THE CONSOLIDATION STRATEGY BETWEEN BANKS AND INSURANCE COMPANY- CASE OF ALGERIA . - Tarik Hamoul , Wafia Zair; Amine Mokhefi (International Journal of Research Science and Management, 2018)
This is an era of unprecedented change for the finance sector. New technologies, new customer expectations, new regulations and new competitive pressures are rapidly disrupting the traditional finance business model. In this environment, insurance and bank organizations have no choice but to adapt. Insurers and banks have been working together for years developing and evolving some consolidations strategy as the bancassurance models. With whole-scale change around the corner for both parts of the financial services sector, to survive and thrive they now need to take what they have learned and adapt and evolve quicker and better than ever before. At the same time, insurers are increasingly starting to recognize that their current organizational structure and culture may not be conducive to achieving the type of real, sustainable and value- creating change and innovation needed to compete in this new world. New models, new ideas and new partners must be found. Executives are starting to recognize the power of alliances